2021
DOI: 10.1016/j.chemosphere.2021.130286
|View full text |Cite
|
Sign up to set email alerts
|

Air pollutants and their degradation of a historic building in the largest metropolitan area in Latin America

Abstract: Historic buildings that comprise the cultural heritage of humanity are in need of preservation on a worldwide scale in regard to degradation resultant from atmospheric pollutants. The Brazilian Public Market, located in the historic center of the mega city of Sao Paulo, is the object of this research, due to its representation of historical Brazilian architecture. The general objective of this manuscript is to analyze the influence of air pollutants on the degradation of the historic Sao Paulo Public Market in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“… Neckel et al (2021) demonstrated that the lack of treatment of these gaseous elements leads to the accumulation of contaminants in the localized atmosphere as the natural process of decay proceeds. Silva et al (2020) , Duarte (2021) and Oliveira et al (2021) warn that gases and other contaminants are added to Accumulated Ultrafine Particles (UFPs) and Nanoparticles (NPs) that are easily transported to other regions through wind action, spreading these harmful contaminants far and wide.…”
Section: Introductionmentioning
confidence: 99%
“… Neckel et al (2021) demonstrated that the lack of treatment of these gaseous elements leads to the accumulation of contaminants in the localized atmosphere as the natural process of decay proceeds. Silva et al (2020) , Duarte (2021) and Oliveira et al (2021) warn that gases and other contaminants are added to Accumulated Ultrafine Particles (UFPs) and Nanoparticles (NPs) that are easily transported to other regions through wind action, spreading these harmful contaminants far and wide.…”
Section: Introductionmentioning
confidence: 99%
“…The greater precision of the variations that occur in natural ventilation in this study was based on the use of a virtual “grid” with 198 points located at the following three heights above the ground level: 0.5 m, 1.27 m and 2.04 m. Sample points were conducted in triplicate, totaling 594 sample points for calculating and modeling the velocity of internal air flow powered only by natural ventilation, with Cluster analyses in different locations both inside and outside of the room. The choice of the three heights (0.5 m, 1.27 m and 2.04 m) utilized for Independência Hospital was based on the work of Silva et al, 2020 , Oliveira et al, 2021 , who consider the presence of contamination in ultrafine particles suspended in the air. The three specific heights were derived from the human scale – heights at which air would enter the respiratory system of average sized humans ( Shao et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…These airborne particles are susceptible to movement from one region to another based on the intensity of wind’s velocity. According to Silva et al, 2020 , Oliveira et al, 2021 air quality studies on a global scale are indispensable. Therefore, our study as well as the work of Carraturo et al (2020) alert that natural ventilation in hospitals dedicated primarily or solely to the care of patients infected with SARS-CoV-2, requires proactive design and preventative care, as these are environments that concentrate high amounts of viral particles in the air and allow those particles to settle onto surfaces if air flow velocity is not adequate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations